2007
DOI: 10.1016/j.juro.2007.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Type A in Combination With Standard Urotherapy for Children With Dysfunctional Voiding

Abstract: Our study demonstrates that the voiding mechanism in children with dysfunctional voiding refractory to standard therapy can be significantly improved and maintained at least 6 months after combined botulinum toxin type A injection and bladder rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 11 publications
0
16
0
3
Order By: Relevance
“…Promising data on the efficacy of botox injections into the external sphincter have been reported in a small group of children with DV resistant to other therapies [66, 67]. BTA leads to temporary paralysis of the external sphincter and may decrease functional bladder outlet obstruction.…”
Section: Day Wettingmentioning
confidence: 99%
“…Promising data on the efficacy of botox injections into the external sphincter have been reported in a small group of children with DV resistant to other therapies [66, 67]. BTA leads to temporary paralysis of the external sphincter and may decrease functional bladder outlet obstruction.…”
Section: Day Wettingmentioning
confidence: 99%
“…However, patients were selected purely on a clinical basis without the use of uroflowmetry or EMG. For patients refractory to biofeedback and α blockers, Radojicic et al [29] and Petronijevic et al [30] have demonstrated temporary clinical and urodynamic efficacy injecting botulinum toxin type A into the pelvic floor and/or external sphincter. An interesting approach that could be applied to refractory cases is the use of intermittent catheterization; Pohl et al [31] showed that once accepted and performed, intermittent catheterization was able to control incontinence in 16 children.…”
Section: Refractory Dysfunctional Voidingmentioning
confidence: 99%
“…The authors reported improved voiding pattern though unlike the preceding study there were limited data quantifying the changes following injection. The more recent and smaller study by Petronijevic et al addressed the possible role of botulinum toxin in conjunction with standard therapy for nine girls with refractory voiding dysfunction, with uroflowmetry and symptom score assessment at 6 months [38]. The authors of these papers did acknowledge the paucity of long-term data, and need to establish whether restoration of normal voiding was maintained.…”
Section: Sphincter Dysfunctionmentioning
confidence: 99%